The Bronze Age begins : the ceramics revolution of early Minoan I and the new forms of wealth that transformed prehistoric society - Betancourt, Philip P. (INSTAP Academic Press, 2008)
The change in ceramic technology in EM I -- The clays and the fired fabrics -- The pottery shapes -- EM I surface treatments and decoration and their relation to fabrics, shapes, and methods of manufacture -- Comments and conclusions on the pottery -- The transformation of Cretan society